Determinants of Profit Growth In Manufacturing Industry Basic and Chemical Sub-Sector in Indonesia - Haryasena Gusti Andayu; Lis Sintha; Abdurrahman Abdurrahman; Agus Munandar (Institute of Computer Science (IOCS), 2022)
This study aims to estimate the effect of liquidity as measured by Current Ratio (CR), solvency as measured by Current Liabilities Inventory (CLI), activity as measured by Total Assets Turnover (TAT), profitability as measured by Net Profit Margin (NPM), sales growth ( SG), and firm size (FZ) on profit growth (PG) with share price (SP) as the intervening variable. The research population is 62 basic and chemical sector companies listed on the Indonesia Stock Exchange (IDX) from 2017-2021. The data estimation method uses smart PLS SEM. Empirical findings show that the ratios of CR, CLI, TAT, NPM, SG, FZ and SP do not affect the company's PG. Then CLI, NPM and FZ have a significant effect on SP and CR, TAT and SG are factors that do not affect SP. SP does not mediate CR, CLI, TAT, NPM, SG and FZ in their effect on PG. The results of this study imply that an increase in company profits can be achieved if the company operates efficiently in order to encourage higher growth.